Robust and Elastic Bioinspired MXene‐Coated Foams with Enhanced Energy Storage and Conversion Capabilities. Issue 8 (29th January 2023) - Jiang, Degang; Bacal, Christine Jurene O.; Usman, Ken Aldren S.; Zhang, Jizhen; Qin, Si; Hegh, Dylan; Lei, Weiwei; Liu, Jingquan; Razal, Joselito M.
Abstract: Constructing highly porous structures using Ti3 C2 Tx MXene provides a promising strategy toward achieving low density, high specific surface area, and shorter ion/molecule transport paths. However, the weak MXene‐MXene or MXene‐substrate interactions hinder the development of ultra‐robust and elastic MXene‐based architectures. To address this issue, a bio‐inspired strategy is developed to effectively adhere the MXene nanosheets onto melamine foam via covalent and hydrogen bonding interactions through polyethyleneimine/polydopamine‐modification. The enhanced interactions contribute to high MXene loading (≈94 wt.%) and reversible compressibility even after 10 000 compression/release cycles at 80% strain. The compressible supercapacitor device assembled from this foam exhibits high energy storage capability (119 F g −1 at 2 mV s −1 ) with capacitance retention of ≈93% after 1000 compression/release cycles at 50% strain. Moreover, the presence of polydopamine and MXene enable the absorption of light in the UV–Vis and near‐IR regions, respectively, inducing photothermal conversion functionality, with an evaporation rate of ≈1.5 kg m −2 h −1 and ≈89% solar evaporation efficiency under one sun illumination. It is envisaged that this bio‐inspired chemical modification offers a versatile strategy for the assembly of MXene nanosheets onto different substrates for various applications, such as electromagnetic interference shielding, energy storage, and conversion. Abstract : An ultra‐robust and elastic MXene based foam is fabricated by using a facial and bioinspired template strategy, which demonstrates high MXene loading (≈93.6 wt.%) and reversible compressibility even after 10 000 compression/release cycles at high strain of 80%. Given these superior attributes, the as‐prepared foam can be used for compressible supercapacitors or steam generation applications.